ISOLATION OF Escherichia coli FROM VANAME SHRIMP (Litopenaeus vannamei) POND AND THE SENSITIVITY TOWARD ANTIBIOTICS - Putri, Resty Fauziah; Nursyirwani, Nursyirwani; Batubara, Ummi Mardhiah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
Vannamei shrimp (Litopenaeus vannamei) is a fishery commodity widely cultivated in various parts of Indonesia. The main problem often found in vannamei shrimp production is poor water quality during the rearing period. This study aims to isolate and identify E. coli contained in water, sediment, and meat of vannamei shrimp cultivated in shrimp ponds and examine its sensitivity to antibiotics. The research was conducted from March to May 2023 at the Technical Implementation Unit (UPT) Vannamei Shrimp Ponds of the Maritime Affairs and Fisheries Service, Tanjung Punak Village, Rupat Utara District, Bengkalis Regency, Riau. The survey method was used in this study. The Most Probable Number (MPN) method was employed for E. coli isolation to calculate bacterial density, and the Kirby-Bauer method was used to test bacterial sensitivity to antibiotics. Based on the identification of the six isolates carried out, it was found that only two isolates were positively identified as E. coli bacteria, namely SD C 3.1 and IP B 1.1, which were isolated from sediment and the Wastewater Treatment Plant (WWTP) pond. The diameter of the inhibition zone for sediment isolate RF01 against the antibiotic chloramphenicol was 18.75 mm, indicating intermediate sensitivity. On the other hand, WWTP isolates RF02 exhibited an inhibition zone of 17 mm for chloramphenicol, indicating medium sensitivity as well. However, it showed resistance to penicillin with a diameter of 6.5 mm and resistance to ampicillin with a diameter of 2 mm.